PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, LOKASI TERHADAP KEPUASAN KONSUMEN DAN DAMPAKNYA PADA MINAT BELI ULANG (PADA RUMAH MAKAN “ERA MINANG” TEMBALANG, SEMARANG) - Rafika Amalia, 14.05.51.0225; Maskur, Ali (Students' Journal of Accounting and Banking, 2018)
This study aims to examine Product Quality, Price Perceptions, Location of Consumer Satisfaction and the impact on Consumer Buying Interest. The population used in this study are consumers of Rumah Makan “Era Minang” Tembalang Semarang.The sample in this study were consumers who had made a purchase decision on Rumah Makan “Era Minang” Tembalang Semarang as many as 100 people.Test equipment in this study uses multiple linear regression.Product quality, price perception and location has a positive and significant impact on customer satisfaction. Customer satisfaction has a positive and significant impact on buying interest. Keywords : Product quality, Price perceptions, location, Consumer satisfaction and consumer buying interest.